AGEs-Induced Calcification and Apoptosis in Human Vascular Smooth Muscle Cells Is Reversed by Inhibition of Autophagy - Hu-Qiang He; Hu-Qiang He; Yuan-Qing Qu; Betty Yuen Kwan Law; Betty Yuen Kwan Law; Cong-ling Qiu; Yu Han; Ivo Ricardo de Seabra Rodrigues Dias; Yong Liu; Jie Zhang; Jie Zhang; An-Guo Wu; et al. (Frontiers Media S.A., 2021)
Vascular calcification (VC) in macrovascular and peripheral blood vessels is one of the main factors leading to diabetes mellitus (DM) and death. Apart from the induction of vascular calcification, advanced glycation end products (AGEs) have also been reported to modulate autophagy and apoptosis in DM. Autophagy plays a role in maintaining the stabilization of the external and internal microenvironment. This process is vital for regulating arteriosclerosis. However, the internal mechanisms of this pathogenic process are still unclear. Besides, the relationship among autophagy, apoptosis, and calcification in HASMCs upon AGEs exposure has not been reported in detail. In this study, we established a calcification model of SMC through the intervention of AGEs. It was found that the calcification was upregulated in AGEs treated HASMCs when autophagy and apoptosis were activated. In the country, AGEs-activated calcification and apoptosis were suppressed in Atg7 knockout cells or pretreated with wortmannin (WM), an autophagy inhibitor. These results provide new insights to conduct further investigations on the potential clinical applications for autophagy inhibitors in the treatment of diabetes-related vascular calcification.